Women in management positions in the hotel industry in Singapore - Lee, Mei Hwa. (2008)
The number of women in management has been increasing over the decades, especially in the hotel industry. However, their career advancement does not seem to be as clear and direct as for their male counterparts. This research is undertaken to find out the general profile of women in management in the hotel industry in Singapore, the types of obstacles they encountered in their career, whether the obstacles cause the existence of the glass ceiling and how the different demographic factors affect the types of obstacles encountered.